Gambaran Leukosit Darah Ikan Koi (Cyprinus carpio) yang Terinfestasi Ichthyophthirius multifiliis pada Derajat Infestasi yang Berbeda dengan Metode Kohabitasi [Leukocyte Profil of Koi Fish (Cyprinus carpio) Which Infested by Ichthyophthirius multifiliis on The Different Infestation Degree With Cohabitation Methode] - Gunanti Mahasri; Pristita Widyastuti; Laksmi Sulmartiwi (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract Koi fish (Cyprinus carpio) is one type of ornamental fresh water, which much liked because of its beauty such as have shape, colour and beautiful patern, so many people depend on their life from culturing and marketing koi fish. The main obstacle in koi fish culture is disease attack. The disease caused by interaction between host, pathogen and environment (Fisheries and Marine Department, 2005). Ichthyophthirius multifiliis (I. multifiliis) is one of parasite which can cause fish ichtyopthiriasis. According Durborow (1998) said, that clinical sign of koi fish who affected by I. multifiliis had a white spot. I. multifiliis is a parasite that eat blood cells (Dogiel et al., 1970). According Macdonald et al., (2001) in Saptanto (2004) explain, that parasite infestation also could increase eosinophile. Total of monocyte increases if there are a foreign substantion in tissue or blood circulation and neutrophile are phagocyte which could migration in the other tissue to eat bacteria (Moyle and Chech, 2004). Meyer and Harvey (1998) in Salasia (2001) assert, that blood test also useful to help disease diagnose, examining immune system and to determine fish health status. The method was used in this field research is experimental method by cohabitation method. This research is expected to provide information and knowledge about leucocyte component which infested by I. multifiliis at different infestation level with cohabitation method. This research was done July 26, 2010 until December 31, 2010 at Klepon Village, District of Garum, Blitar, East Java and in  the Laboratory of Education Faculty of Fisheries and Marine Fisheries, Airlangga University, Surabaya. I. multifiliis infestation level are classified based on the total of I. multifiliis who infestation koi fish total of low: 1–5 parasites/slide, medium: 6–10 parasites/slide, High: more than 11 parasites/slide (Margolis et al., 1982 in Akter dkk., 2007). The result of research showed that chages of leucocyte blood profil of the amount the total each leucocyte component (lymphocyte, neutrophile, monocyte, eosinophile) koi fish who infested by I. multifiliis, there is a declining in average percentage of total lymphocyte in low infestation 86.20%, medium infestation 79.40% and heavy infestation 75.20%. The average percentages of total monocyte was increasing in low infestation 5.40%, medium infestation 5.60% and heavy infestation 6.60%. The average percentages of total neutrophile also increasing in low infestation 6.40%, medium infestation 11.20% and heavy infestation 11.60%. The average percentages of total eosinophile also increasing in low infestation 2.00%, medium infestation 3.60% and heavy infestation 5.60%. water oquality measured during research, the average of temperature 24-26C and pH cohabitation 8.